The role of S100A8 and S100A9 in external auditory canal cholesteatoma - He, Guanwen; Han, Weijing; Zhu, Zhongshou; Wei, Rifu; Lin, Chang (Frontiers in Immunology, 2024)
Background: Studies indicated that diverse cellular mechanisms including epithelial migration and hyper-proliferation, inflammatory responses and enzymatic bone erosion were involved in the pathogenesis of cholesteatoma. S100A8 and S100A9, which are Ca2+ binding proteins belonging to the S100 family, can trigger the signaling pathways involved in the inflammatory processes and variety of cellular processes includes cell cycle progression, proliferation and cell migration. However, the role of S100A8 and S100A9 and their associated inflammation and other signaling pathways in cholesteatoma have not been investigated yet. This study aimed to investigate that the role of S100A8 and S100A9 in external auditory canal cholesteatoma and its potential pathological mechanisms. Methods：The study conducted histological staining, immunostaining, PCR and western blot to investigate the expression S100A8/A9 and its related pathways in clinic EACC and murine model of EACC. Results：Our data showed that there was an increased mRNA and protein level of S100A8 and S100A9 in clinical and animal model of EACC and the S100A8/A9 heterodimer protein was increased in EACC model. Our study further demonstrated that the increased S100A8 and S100A9 were associated with apoptosis, inflammatory (TGF-β, IFN-γ and IL-10) and angiogenetic (VEGF, HGF/SF and c-Met) molecular pathways. The correlation analysis indicated that S100A8 and S100A9 were correlated to clinic staging, apoptosis, inflammatory and angiogenetic factors. Conclusion：This study provided novel insight into the role of S100A8 and S100A9 associated with pathological mechanisms of EACC.